Delayed open conversion after endovascular aortic repair. (February 2019) - Law, Y; Chan, YC; Cheng, SW
Aim: We present the clinical outcomes of patients who underwent delayed (>30 days) open surgical repair after endovascular aortic aneurysm repair. Methods: All patients receiving delayed open repair of infrarenal and juxtarenal aortic aneurysms after endovascular repair from July 2001 to December 2017 were retrospectively reviewed. Patients' baseline characteristics, indications for delayed open conversion, and time between endovascular repair and open conversion are described. Early outcomes included operative approach, morbidity, and mortality. Midterm outcomes included survival. Results: Twenty-two (3.3%) of 667 patients with prior infrarenal endovascular aortic aneurysm repair had delayed open conversion (20 elective and 2 emergency). The time from endovascular repair to open conversion was 60 ± 36 months. The indications were 6 (27%) type Ia endoleaks, 6 (27%) type II endoleaks with enlarging sac size, 2 (9%) endotensions, 7 (32%) unknown types of endoleak, and 1 (5%) graft infection. The 7 minutes unknown endoleaks were confirmed as lumbar leaks in 4 cases and fabric leaks in 3. Operative time was 222 ± 48 min with blood loss of 2211 ± 2057 mL. Hospital stay after conversion was 12 ± 8 days. There was no 30-day mortality. Estimated survival rates were 96%, 91%, 86%, 79% and 57% at 1, 2, 3, 4, and 5 years postoperatively. Conclusion: Delayed conversion to open surgery after endovascular aortic aneurysm repair by endograft explantation appears to be safe with good short- and mid-term outcomes. With careful preoperative assessment, open conversion remained a realistic and viable option in patients with failed endovascular treatment.